Current controversies in prenatal diagnosis 1: should NIPT routinely include microdeletions/microduplications?†. (19th November 2015) - Rose, Nancy C.; Benn, Peter; Milunsky, Aubrey
Abstract : What's already known about this topic? Technology is available to add microdeletion testing to cell free DNA screening. What does this study adds? This report summarizes an oral debate presented at the 19th International Conference on Prenatal Diagnosis and Therapy in Washington, DC, USA, on 14 July 2015. Through the debate, the benefits, limitations, and challenges of potential wide‐scale implementation of microdeletion testing with prenatal samples was reviewed and discussed.